KURIKULUM MERDEKA DAN INTERNALISASI NILAI AKHLAKUL KARIMAH MELALUI P5 - Hasibuan, Lukman; Zulhammi, Zulhammi; Hasibuan, Zainal Efendi; Yuda, Fatti Miarni; Endayana, Bestari (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2024)
This research is motivated by the project to strengthen the Pancasila student profile (P5) implemented at SMP Negeri 3 Pandan has been running and has been implemented by completing several themes contained in the school agreement, however, researchers still find several things that must be refined and adjusted and it is necessary to strengthen akhlakul karimah education for students. The purpose of this study is to see the development of an independent curriculum at SMP Negeri 3 Pandan that will prioritize the concept of the first Pancasila profile, namely Believing, fearing God Almighty, and having noble character at SMP Negeri 3 Pandan. ADDIE model research methodology, namely: Analysis, Design, Development, Implementation and Evaluation. The results showed that communication between school community members in policy development has been carried out very well, SMP Negeri 3 Pandan has human resources (educators and education personnel) who have good qualifications and learning facility resources are very good, attitudes or dispositions to respond to policies have been accepted and carried out very well, and a bureaucratic structure that is good at carrying out its duties, and has an SOP for the Pancasila Student Profile Strengthening Project (P5) according to the independent curriculum applied in class VII. Support for the development of the Pancasila Student Profile Strengthening Project (P5) comes from cooperation between school members who support project-based learning, as well as support from external parties to realize national-level projects. The obstacles encountered only lie in the lack of references related to the Pancasila Student Profile Strengthening Project (P5) from the government, so that educators must be more creative and innovative in creating meaningful learning projects. SMP Negeri 3 Pandan in developing the Pancasila Student Profile Strengthening Project (P5) makes teaching modules that are in accordance with the learning objectives of the project. Then, this Pancasila Student project has 6 aspects where each aspect is realized in school co-curricular learning.ABSTRAKPenelitian ini dilatar belakangi oleh proyek penguatan profil pelajar Pancasila (P5) yang dilaksanakan di SMP Negeri 3 Pandan telah berjalan dan telah dilaksanakan dengan menyelesaikan beberapa tema yang tertuang dalam kesepakatan sekolah akan tetapi, peneliti masih mendapati beberapa hal yang harus disempurnakan dan disesuaikan dan dibutuhkan penguatan pendidikan akhlakul karimah bagi peserta didik. Tujuan penelitian ini adalah untuk melihat pengembangan kurikulum merdeka di SMP Negeri 3 Pandan akan mengedepankan konsep profil pancasila yang pertama yakni Beriman, bertakwa kepada Tuhan Yang Maha Esa, dan berakhlak mulia di SMP Negeri 3 Pandan. Metodologi penelitian model ADDIE, yaitu: Analysis, Design, Development, Implementation dan Evaluation. Hasil penelitian menunjukkan bahwa komunikasi antar warga sekolah dalam Pengembangan kebijakan sudah dilaksanakan dengan sangat baik, SMP Negeri 3 Pandan memiliki sumber daya manusia (pendidik dan tenaga kependidikan) yang memiliki kualifikasi bagus dan sumber daya fasilitas pembelajaran sudah sangat baik, sikap atau disposisi untuk menyikapi kebijakan-kebijakan sudah diterima dan dijalankan dengan sangat baik, dan struktur birokrasi yang sudah baik dalam menjalankan tugasnya, serta memiliki SOP Projek Penguatan Profil Pelajar Pancasila (P5) sesuai kurikulum  merdeka yang diterapkan di kelas VII. Dukungan Pengembangan Projek Penguatan Profil Pelajar Pancasila (P5) berasal dari kerjasama antar warga sekolah yang mendukung adanya pembelajaran berbasis projek, serta dukungan pihak eksternal untuk mewujudkan projek berbasis taraf Nasional. Hambatan yang ditemui hanya terletak pada kurangnya referensi terkait Projek Penguatan Profil Pelajar Pancasila (P5) dari pemerintah, sehingga pendidik harus lebih kreatif dan inovatif menciptakan  projek pembelajaran yang bermakna. SMP Negeri 3 Pandan dalam mengembangkan ojek Penguatan Profil Pelajar Pancasila (P5) membuat modul ajar yang sesuai dengan tujuan pembelajaran projek. Kemudian, projek Pelajar Pancasila ini memiliki 6 aspek dimana setiap aspek tersebut diwujudkan dalam pembelajaran kokurikuler sekolah.